An In Situ Artificial Cathode Electrolyte Interphase Strategy for Suppressing Cathode Dissolution in Aqueous Zinc Ion Batteries. Issue 6 (28th April 2021) - Zhang, Lishang; Zhang, Bao; Hu, Jisong; Liu, Jia; Miao, Ling; Jiang, Jianjun
Abstract: Rechargeable aqueous zinc ion batteries have attracted increasing attention as a new energy storage system because of the high ionic conductivity and safe aqueous electrolyte. The spontaneous vanadium dissolution in aqueous electrolytes is one major problem because the water with serious polarity would corrode the crystal structure of vanadium‐based cathodes. Here, an in situ artificial cathode electrolyte interphase (CEI) strategy is proposed to kinetically suppress the vanadium dissolution in aqueous zinc ion batteries. The strontium ion is introduced into vanadium oxide layers as a sacrifice guest, which would directly precipitate upon getting out from the vanadium‐based cathode to in situ from a CEI coating layer on the surface. This strategy is proven with the help of various technologies, and the remarkable ability of the CEI layer to suppress cathode dissolution is evaluated by multiple electrochemical and chemical methods. As a result, the cathode after CEI conversion exhibits the best recharge capacity retention after open circuit voltage rest for 3 days in comparison with other cathodes. This work reports a general strategy to construct the electrode‐electrolyte interface for suppressing vanadium‐based cathodes dissolution in aqueous electrolytes and beyond. Abstract : The spontaneous vanadium dissolution in aqueous electrolytes is one major problem in aqueous batteries. Here, an in situ artificial cathode electrolyte interphase (CEI) strategy is proposed to kinetically suppress the vanadium dissolution. This strategy is proven with the help of various technologies, and the CEI layer is verified to suppress cathode dissolution and prolong the cells' lifespan.